An Ethnographic Analysis of Escort Services in Poland: An Interactionist Approach - Ślęzak, Izabela (Qualitative Sociology Review, 2020)
In the Polish literature on the subject, prostitution is analyzed from various theoretical perspectives, but, first of all, from the perspective of social pathology. This approach makes the researchers focus mainly on the social maladjustment of women providing sex services and the reasons for their violation of the normative order.In my ethnographic research conducted in escort agencies in Poland, I was willing to go beyond this narrow outlook. I have adapted an interactionist perspective to analyze the escort agencies as organizations where intense interactions between employees, as well as employees and clients, take place, the sex work process is organized, and the meanings of prostitution are negotiated. I conducted the analysis according to the procedures of the grounded theory methodology. It allowed me to see and describe such processes as: (re)defining the situation of providing sex services from vice to work, sex work as a collective action, performing sex work, secondary socialization for sex work.The adaption of an interactionist perspective opens some new directions for analysis, which could help to understand the phenomenon of women getting involved in and continuing to provide sex services for a long time.